Spliceosome-mediated decay (SMD) regulates expression of nonintronic genes in budding yeast. - Volanakis, A; Passoni, M; Hector, R; Shah, S; Kilchert, C; Granneman, S; Vasiljeva, L (2013)
We uncovered a novel role for the spliceosome in regulating mRNA expression levels that involves splicing coupled to RNA decay, which we refer to as spliceosome-mediated decay (SMD). Our transcriptome-wide studies identified numerous transcripts that are not known to have introns but are spliced by the spliceosome at canonical splice sites in Saccharomyces cerevisiae. Products of SMD are primarily degraded by the nuclear RNA surveillance machinery. We demonstrate that SMD can significantly down-regulate mRNA levels; splicing at canonical splice sites in the bromodomain factor 2 (BDF2) transcript reduced transcript levels roughly threefold by generating unstable products that are rapidly degraded by the nuclear surveillance machinery. Regulation of BDF2 mRNA levels by SMD requires Bdf1, a functionally redundant Bdf2 paralog that plays a role in recruiting the spliceosome to the BDF2 mRNA. Interestingly, mutating BDF2 5' splice site and branch point consensus sequences partially suppresses the bdf1Δ temperature-sensitive phenotype, suggesting that maintaining proper levels of Bdf2 via SMD is biologically important. We propose that the spliceosome can also repress protein-coding gene expression by promoting nuclear turnover of spliced RNA products and provide an insight for coordinated regulation of Bdf1 and Bdf2 levels in the cell.